2018
DOI: 10.1051/epjn/2018021
|View full text |Cite
|
Sign up to set email alerts
|

Cross section covariances: a user perspective

Abstract: This paper makes a brief historical review, from the user point of view, of the impact of the different covariance data made available during this period, then look at today current situation in the different evaluated files, using practical examples. In particular, the performance, in terms of C/E, of two of the most recent and reliable evaluate files, CIELO and CIELO-2, is presented for a set of selected integral experiments. Moreover, this performance is compared for consistency against the uncertainty comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Reduced confidence in the fission cross section can have real consequences for the allowed power level and operating regimes for these systems. A study conducted by SG46 (126) found that many individual reactions were modified by several percent from ENDF/B-VII.1 to ENDF/B-VIII.0. Figure 8 shows some examples.…”
Section: Nuclear Energymentioning
confidence: 99%
“…Reduced confidence in the fission cross section can have real consequences for the allowed power level and operating regimes for these systems. A study conducted by SG46 (126) found that many individual reactions were modified by several percent from ENDF/B-VII.1 to ENDF/B-VIII.0. Figure 8 shows some examples.…”
Section: Nuclear Energymentioning
confidence: 99%
“…The next essential ingredient of DA À prior uncertainties À is crucial for any Bayesian inference technique [1,19,[35][36][37].…”
Section: Information Content Of the Posterior Bias And Uncertaintiesmentioning
confidence: 99%
“…In fact, DA integrate somehow an information brought with the used IEs onto corrected nuclear parameters and their uncertainties [35]. In the years of DA practical implementations an intensive discussion arisen on the question how to interpret an appearance in posterior CND cross-covariance members have not been in prior ones [36]. It was found that the crosscovariance members in a posterior CND always contain the traces of IEs data [1,19,36,37], characterizing in certain extent an efficiency of the adjustment [19].…”
Section: Information Content Of the Posterior Bias And Uncertaintiesmentioning
confidence: 99%
“…To quantify effectiveness of integral data available for us to test evaluated nuclear data, we propose methods to quantify independency of a set of integral data, to choose a minimum set of proper integral data from a huge amount of integral data, and to quantify possibility of validation of each nuclear data with a given set of integral data. Furthermore, this concept is utilized to interpret the nuclear data compensation effect [6], which has been recently raised in the community of nuclear data.…”
Section: Introductionmentioning
confidence: 99%